Elucidation of the pathways underlying the spectrum of cancers affecting different tissues in lynch syndrome - Krause, May (Department of Pathology, 2025)
Lynch Syndrome (LS) is a hereditary disorder that predisposes individuals to an increased risk of several cancers, particularly colorectal cancer (CRC) and endometrial cancer (EC). LS arises from constitutional (“germline”) pathogenic variants affecting one of four DNA mismatch repair (MMR) genes. When coupled with somatic mutations (“second hits”) in tumours affecting the same gene, this results in deficient MMR. However, the mechanisms by which MMR deficiency contribute to cancer development remain unclear. This thesis aims to improve LS ascertainment by investigating driver genes and dysregulated pathways in CRC, EC and breast cancer (BC) and to address whether BC may be part of the LS cancer spectrum. Furthermore, it aims to identify subtype-specific drugs targeting these pathways. Using somatic data from cBioPortal (https://www.cbioportal.org), samples were triaged as likely LS (LLS) or likely sporadic (LSp), with computational analyses providing molecular insights into the subtypes of LS-associated cancers. Key analyses included differential expression, pathway enrichment, kinase activity, mutational signatures, and drug sensitivity assessments to characterise cancer subtypes. The study identified PI3-Akt and Wnt signalling as dysregulated in LLS-CRC and LSp-CRC, respectively. Similar analyses in EC and BC revealed that the TGF-beta and cAMP signalling pathways were notably dysregulated in LLS and LSp subtypes, respectively, for both EC and BC, supporting the inclusion of BC within the LS spectrum. Drug sensitivity analysis showed that cell lines with higher dependency on key pathways exhibited increased sensitivity to corresponding inhibitors, suggesting potential therapeutic targets in LS-associated cancers. This study elucidates key driver genes, dysregulated pathways and drug sensitivities in LS- associated cancers, offering insights into the molecular mechanisms driving these cancers. Variations in pathway enrichment and drug responses between LLS and LSp cases across cancer types suggest new therapeutic avenues and underscore the importance of personalised treatment strategies based on cancer subtype, genetic profile, and pathway dependencies.